(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
It was found that during the restenosis process occurring in the poststen ting period of coronary arteries, the activation of integrins in the endothelium and the subsequent interaction of activated cell-surface transmembrane heterodimers with the extracellular matrix lead to increased cell adhesion. Consequently, this results in the transendothelial migration of inflammatory elements, including leukocytes, to the affected areas, contributing to the formation of inflammatory signs in the vessel wall. It was determined that these processes specifically lead to the development of focal vasculitis in the vessel wall after coronary stenting, intensification of reparative regeneration in these areas, active proliferation of fibroblasts, and ultimately, vascular restenosis.